SITUATION OF MEDICAL SOLID WASTE MANAGEMENT AND SOME ASSOCIATED FACTORS IN PHU THO GENERAL HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: To describe the current situation of medical solid waste in Phu Tho General hospital in 2021Methods: Descriptive cross-sectional method with quantitative methods were conducted from 01/2021 to 12/2021 at 16 clinical departments, 3 paraclinical departments and 4 centers at Phu Tho General Hospital.Results: The results indicated that most of the solid waste management at Phu Tho General Hospital have fulfilled the criterial specified in Circular No. 58/2015/TTLT-BYT-BTNMT issued on December 31, 2015. However, there still have some activities, such as there was no waste symbol outside the bin or the instruction for categorization and collecting solid waste. The hospital had 3 teams for solid waste transportation with full equipment but the transportation route from collection area to waste storage and treatment is not separate.
Keywords: Medical solid waste, waste management, general hospital, Phu Tho.